Trade, investment and cooperation in health product and services in the Asia-Pacific Region - Arpita Mukherjee; Eshana Mukherjee; Ramneet Goswami (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2022)
Globally, healthcare is a key sector for the overall well-being of a country and its population. By 2030, at least 60 percent of the global population will be living in Asia, and one in four will be over 60 years of age. As the COVID-19 pandemic highlighted the importance of the sector, it also accentuated the issue of insufficient and unequal access to essential health products and services all across the globe. In Asia-Pacific, over the last few decades, countries have focussed on improving their healthcare sector and have been trying to achieve the targets set by SDG 3 - Ensure Healthy Lives and Promote Wellbeing for All at All Ages, and SDG 17 - Partnership for the Goals. Yet there are still considerable gaps across the countries, in terms of access to healthcare services and per capita healthcare expenditure. The different levels of development among countries and across sub-regions have resulted in a fragmented marketplace, infrastructure gaps in developing and least developed countries (LDCs), limited government funding, multiple regulatory regimes and standards, limited public-private partnerships and shortages of key healthcare products and personnel - some of these issues can be addressed through trade, cross-border investment and collaborations. [...]
Keywords: F13; F15; F20; I18; 330; Healthcare; Asia-Pacific; Trade Agreements; UN SDGs; Collaborations